Education and Improvement of Physical Qualities of Boxers (Eurasian Journal of Learning and Academic Teaching, 2023)
This article examines ways to improve the physical and mental qualities of boxers and work on them. Also improving the technical and tactical skills of highly skilled boxers with the help of non-contact exercises in this article. Through non-contact exercises, athletes must build confidence in their will, strength and capabilities. Further development of technical and tactical skills of boxerstirishga is aimed at clarifying the actual problems of increasing the duration of the oriented methodology.